2013
DOI: 10.1002/cncr.27973
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of contemporary clinical research in muscle‐invasive and metastatic urothelial cancer

Abstract: BACKGROUND: There have been no improvements in the treatment of metastatic urothelial cancer in the past several decades. A census of contemporary clinical research in this disease was performed to identify potential barriers and opportunities. METHODS: These authors performed a search for clinical trials exploring interventions in muscle-invasive and metastatic urothelial cancer, using the ClinicalTrials.gov registry. Data extracted from the registry included title, recruitment status, interventions, sponsor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…[1][2][3][4] In spite of the great progress has been made in the clinical treatment of BCa, the overall survival rate for BCa patients is still pessimistic. [5][6][7][8] The prognosis of BCa patients is closely related to the clinical stage of BCa, but the specific early-stage symptoms for BCa patients are unclear. [9][10][11][12] Thus, it is still urgent to differentiate novel biomarkers for the early diagnosis and efficient treatment for BCa patients.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In spite of the great progress has been made in the clinical treatment of BCa, the overall survival rate for BCa patients is still pessimistic. [5][6][7][8] The prognosis of BCa patients is closely related to the clinical stage of BCa, but the specific early-stage symptoms for BCa patients are unclear. [9][10][11][12] Thus, it is still urgent to differentiate novel biomarkers for the early diagnosis and efficient treatment for BCa patients.…”
Section: Introductionmentioning
confidence: 99%
“…Adjuvant cisplatin-based chemotherapy has never been definitively proven to improve overall survival, but it is frequently used. Systemic therapy for metastatic disease has historically consisted of platinum-based chemotherapy, and this is discussed in the consensus report [ 19 , 20 ]. The following objectives were deemed as priorities for the discussion of the panel meeting for muscle invasive and advanced disease: 1) to define the role of immune checkpoint inhibitors in the treatment of metastatic urothelial cancer, 2) to comment on the clinical utility of biomarkers predictive of benefit to treatment with these therapies, and 3) to discuss potential utility of immune-based therapy in the muscle invasive, non-metastatic setting.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, due to poor accrual, investigators usually design small, single-arm, phase II trials whose results are not likely to change the treatment paradigm, as demonstrated by a 2013 analysis of ongoing trials for metastatic urothelial carcinoma. 12 Based on these observations, the Bladder Cancer Advocacy Network Clinical Trials Working Group released a report emphasizing the urgent need for communication and collaboration among investigators to overcome this major barrier to developing effective treatments for urothelial carcinoma. 12 …”
Section: Barriers To Development Of Effective Therapies For Urotheliamentioning
confidence: 99%
“…12 Based on these observations, the Bladder Cancer Advocacy Network Clinical Trials Working Group released a report emphasizing the urgent need for communication and collaboration among investigators to overcome this major barrier to developing effective treatments for urothelial carcinoma. 12 …”
Section: Barriers To Development Of Effective Therapies For Urotheliamentioning
confidence: 99%